2015
DOI: 10.33697/ajur.2015.008
|View full text |Cite
|
Sign up to set email alerts
|

Does Altering Local Water Availability for an Invasive Plant (Raphanus raphanistrum) Affect Floral Morphology and Reproductive Potential?

Abstract: Abiotic environmental variation can have dramatic effects on plant floral morphology and nectar or pollen rewards. In response, pollinators may change their foraging behavior and distribution and if pollinators change their foraging behavior or distribution, this could have dramatic effects on the reproductive success of plant populations. To start tackling this problem, we measured the response of floral morphology (corolla diameter, stamen length, and ovule number) of Raphanus raphanistrum to experimental ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Despite evidence to suggest soil moisture plays a significant role in Raphanus seed development and fecundity Pirimova et al, 2015), we found surprisingly little effect of experimental watering treatment on seedbank dynamics. Importantly, hybrid populations exhibited germination rates more than double that of wild populations and 58% lower rate of dormancy compared with rates in wild populations (Table 1, Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite evidence to suggest soil moisture plays a significant role in Raphanus seed development and fecundity Pirimova et al, 2015), we found surprisingly little effect of experimental watering treatment on seedbank dynamics. Importantly, hybrid populations exhibited germination rates more than double that of wild populations and 58% lower rate of dormancy compared with rates in wild populations (Table 1, Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…As in Pirimova et al . (), we transplanted cultivated and wild seedlings into 40 plots (F 0 ) (nine cultivated and nine wild seedlings per plot) at Waterman Farm during spring 2010. We planted seedlings in one of four watering treatment plots in a randomised complete block design with one plot per treatment, per block, making five blocks.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, hybridization can occur only when foraging pollinators move between species. Furthermore, in an earlier study we have documented that increased water availability increased corolla diameter and potentially floral attractiveness [46]. We hypothesized that pollinator movements would correlate with actual hybridization events and thus rates of hybridization.…”
Section: Discussionmentioning
confidence: 97%
“…Our recent work has documented that R . raphanistrum corolla diameter and flower production decreases with decreasing soil moisture [45, 46]. Thus, shifts in hybridization rates may be a consequence of a series of plant responses to local environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We wanted to determine whether the relative success of hybrids during invasion can be driven by both genetic and environmental variation in the habitat and ecological context of populations. As a hypothetical scenario, variation in water availability may alter plant size and/or the number of flowers produced by a plant, hence affecting the amounts of ovules and pollen produced (Conner et al, 1996a,b; Campbell et al, 2015; Pirimova et al, 2015; Younginger et al, 2017), and/or the number or size of seeds produced (e.g., Humara et al, 2002). Differences in pollen and seed production are known to drive differences in short‐term gene flow among populations (Loveless and Hamrick, 1984; Campbell, 1985; Brunet and Sweet, 2006).…”
Section: Location and Year Min Temp (°C) Avg Temp (°C) Max Temp (°C) Cumulative Rainfall (Cm)mentioning
confidence: 99%